Restrictions on the Exercising of Human and Civil Rights and Freedoms Due to Cybersecurity Issues - Małgorzata Czuryk (Studia Iuridica Lublinensia, 2022)
Human rights and freedoms may be restricted in particular circumstances. The restrictions in question are not general, as they may be applied only exceptionally for the protection of more significant interests. One interest which provides grounds for the imposition of restrictions is cybersecurity. The legislator does not explicitly define cybersecurity as a premise for restrictions on human and civil rights and freedoms, but it does permit such limitations for the sake of State security, the component parts of which include cybersecurity, which is particularly important today, in the Internet era. Threats in cyberspace can result in the enforcement of a state of exception (martial law, state of emergency, or state of natural disaster), under which the exercising of constitutional freedoms and rights may be restricted. In this event, the legislator explicitly states that actions in cyberspace which threaten certain legally protected interests are permitted to result in curbing the freedoms and rights of individuals for the purpose of restoring cybersecurity.